Neuroimaging of working memory dysfunction in schizophrenia:from theory of hypofrontality to dysfunction of default mode network - Pawęzka, Justyna; Karakuła-Juchnowicz, Hanna; Welcz, Henryk (Current Problems of Psychiatry, 2015)
Working memory is the cognitive function which is responsible for maintaining and operating of information in a short period of time. It is of fundamental importance for so-called mental plasticity which is, in turn, is vital for people in changing situation. Many studies have pointed to the impairment of working memory functioning in patients with schizophrenia. This article provides an over-view of approaches to neuroimaging of working memory dysfunction in patients with schizophrenia, starting from the theory of hipofrontality, through the model of neural failure in dorsolateral prefrontal cortex ( inverted U-shaped activation), the model of temporal lobe, disturbances in the interaction between the processes of working memory and long-term memory in schizophrenia, the distributed model of dysfunction, to dysfunction of default mode network.